Large-Transducer Measurements of Wavefront Distortion in the Female Breast - Zhu, Qing; Steinberg, Bernard D. (Ultrasonic imaging, 1992)
Ultrasonic waves propagating through soft tissue experience wavefront distortion. Refraction occurs at boundaries between tissue beds having different sound speeds; scattering occurs within a tissue bed, caused by local impedance variations. This paper describes measurements of wavefront distortion in the human female breast that indicate that refraction is the dominant distortion mechanism when the ultrasonic phased array is very large. The determination that refraction dominates the wavefront distortion is based upon studies of multiple image artifacts that result from a single source radiated through in vivo breasts and breast phantoms. The receiving apertures used were 4.65 and 9.6 cm. Such image artifacts are repeatedly observed in the 10 young subjects reported in this paper, and also in older subjects. An understanding of the in vivo observations is obtained by phantom studies.